Mobile Platform of SRF Production and Electricity and Heat Generation. (December 2015) - Tallini, A.; Vallati, A.; Cedola, L.
Abstract: The technological frontier is ripe for action on the cycle of municipal waste at local level through the optimization of existing treatment processes, adapting to European Union directives. The study concerns the analysis of the waste cycle in order to rationalize the current paths of the waste by adapting to EU directives, with a view of the entire supply chain - from the delivery to the energy production (WtE, Waste to Energy) – with a intermediate stage of SRF (Solid Recovered Fuel) production. The DIMA has developed an innovative platform for MSW treatment (unsorted and not), based on newly developed technologies that enables its weight and volume reduction and the transformation in SRF high quality, by achieving consistent chemical-physical and particle size parameters through the innovative technology of mechanochemical micronization. This standardized fuel product is therefore suitable for energy recovery within the platform using the most advanced gasification process. The study aims at developing a mobile demonstration plant of 100-200 kWe for energy recovery from waste in cogeneration by conversion of MSW into SRF through a system of characterization, treatment and recycling based on a highly innovative mechanochemical refining system. The SRF is enhanced through more advanced gasification process and it can used for the production of electricity and thermal energy. The production, the gasification and the syngas combustion take place in modular units arranged in appropriate mobile units (containers) appropriately configured, to fully meet the objectives of a sustainable policy management and security of waste. b Unit 1 (waste treater - SRF producer) is developed to operate the transformation of industrial waste in SRF for subsequent gasification inside unit 2 (Boiler Gasifier). It carries out a pre-treatment and mechanochemical micronization waste treatment. The SRF is reduced into pellets to be introduced into the 2 (boiler gasifier) to its gasification (syngas production). The pellet (auxiliary unit 4, pellettizer) is gasified in the unit 2 and enriched in order to obtain synmethan gas for producing electricity in the cogeneration unit 3 (energies production).